Distortion of Substantive Justice in Inheritance Distribution: An Islamic Legal Analysis of Unilateral Control over Undivided Estates - Zahro, Safiatus; Rouf, Abd (Sakina: Journal of Family Studies, 2026)
This study examines substantive justice in the management of undivided estates within the framework of Islamic inheritance law. It highlights the gap between the formal recognition of inheritance rights and the actual realization of economic benefits received by heirs when inherited property remains under joint ownership (musyā‘). The study aims to analyze the concept of justice based on the provisions of farā’iḍ and to explain how unilateral control, use, or transfer of inheritance assets may distort substantive justice. A normative-empirical legal research method is employed, using conceptual and case-based approaches. Primary and secondary legal materials serve as the main sources, while empirical data from interviews with two informants are used as limited illustrations of practical conditions in the management of undivided estates. The findings indicate that justice in Islamic inheritance law extends beyond determining heirs and their prescribed shares. It also includes the physical distribution of inherited property and the fair allocation of economic benefits while the estate remains jointly owned. The case analysis reveals indications of substantive justice distortion, such as restricted access to inheritance information, unequal enjoyment of economic benefits, lack of transparency in asset management, and the absence of accountability mechanisms. Theoretically, the study proposes an analytical framework distinguishing three dimensions of inheritance justice: determination of rights, physical division of assets, and distribution of economic benefits from undivided estates. Practically, it emphasizes the need for transparency, full consent of heirs, and proportional distribution of benefits as essential elements of property protection within the concept of maṣlaḥah mursalah.